EPID-12. INCIDENCE AND SURVIVAL TRENDS FOR MEDULLOBLASTOMAS IN THE UNITED STATES FROM 2001 TO 2013. Issue 11 (6th November 2017) - Khanna, Vishesh; Achey, Rebecca; Ostrom, Quinn; Block-Beach, Hunter; Kruchko, Carol; Barnholtz-Sloan, Jill; de Blank, Peter
Abstract: Population-based data examining recent epidemiological trends in medulloblastoma, the most common pediatric brain malignancy, are limited. Therefore, we sought to examine recent population-level trends in medulloblastoma incidence and survival. Central Brain Tumor Registry of the United States (CBTRUS) data were analyzed from 2001–2013. Age-adjusted incidence rates (IR), annual percent changes (APCs) with 95% confidence intervals (CI) were calculated by age, sex, and race. Relative survival rates were calculated by age, sex, and race using Surveillance, Epidemiology and End-Results (SEER) registries; a subset of CBTRUS data. Kaplan-Meier and Cox proportional hazards models were used to examine survival differences. Medulloblastoma incidence remained relatively stable from 2001–2013, with minor fluctuations from 2001–2009 (APC=2.2, 95%CI: 0.8, 3.5) and 2009–2013 (APC=-4.1, 95%CI: -7.5, -0.6). Incidence was highest in patients aged 1–4 years at diagnosis, but patients aged 10–14 years showed increased incidence from 2000–2013 (APC=3.2, 95%CI: 0.6, 5.8). Males displayed higher IR relative to females (males: 0.16 vs. females: 0.12), except in patients <1 year-old. Compared to Whites, Blacks displayed a non-significant increase in incidence (APC=1.7, 95%CI: -0.4, 4.0) and in mortality risk (hazard ratio for survival =0.74; p=0.09). The current study reports no overall change in medulloblastoma incidence from 2001–2013. Male and female patients <1 year-old had equal medulloblastoma incidence rates and poor 5-year relative survival compared to other ages. Non-significant trends in the data suggest disparities in medulloblastoma incidence and survival by race. Thus, analysis of tumor-specific trends by demographic variables can uncover clinically informative trends in cancer burden.